Determinan Kadar Cluster Diferensiasi 4 (CD4) pada Orang dengan HIV/AIDS - Rico Januar Sitorus; Chairil Anwar; Imelda Purba; Merry Natalia (Jurnal Kesehatan, 2021)
AIDS which is caused by the human immunodeficiency virus (HIV), is a global health crisis, with differentiated cluster 4 (CD4) cells being the main target so that it can affect the high morbidity and mortality rates. This study aimed to determine the determinants that affect CD4 levels in people with HIV/AIDS. The study population was all people with HIV/AIDS in care, support, and treatment (CST) services in Palembang City with a sample size of 118. The sampling technique was carried out using nonrandom, namely purposive sampling. Samples were taken when respondents took antiretroviral (ARV) treatment at a health facility. The research instrument used a structured questionnaire and medical records. To measure the determinant (independent variable) was done by interview, while to determine the CD4 count using data that has been recorded in the Medical Record. The results are the length of treatment was a factor that could reduce the risk of low CD4 levels in people with HIV/AIDS, with p-value=0,006; ORAdj 0,286 (0,117-0,697), whereas stigma and treatment side effects were proven as confounding variables. Increasing the CD4 in people living with HIV/AIDS requires appropriate and regular treatment. Regular treatment with a duration of therapy of more than 1 year has been shown to prevent low CD4 cells. The higher the CD4 cell count in people living with HIV/AIDS, the greater the chance of controlling opportunistic infections, reducing transmission and premature death. People with HIV/AIDS are advised to take regular medication at available health facilities and take medication regularly.